Implementation av skanning i manuella monteringsflöden: Hur skanning kan implementeras med på teknik, användbarhet och lönsamhet - Drott, Mikaela; Nuhic, Sabina (My University, 2021)
A production that is efficient and quality assured is crucial for a company’s success. Implementation of automation, scanning for example, in the production environment is a way for a company to achieve this. Therefore, this study has explored the area of implementation of hand scanning in manual assembly flows, with regards to technical possibilities and limitations, usability, and profitability. Collection of data has mainly taken place through interviews and observations. The rendering of results was an iterative process where problematic work activities were identified and scanning solutions were then developed for the activities that could potentially generate profitability with the aid of scanning. Finally, capital budgeting was used to assess the profitability of a future investment. The study shows that the usefulness of hand scanning in manual assembly flows is contingent on the technical preconditions. It is not a given that scanning leads to increased efficiency and quality in production as it depends not only on the hardware and software, the surrounding information system must also promote good functionality with scanning. Lack of a network connection in the production environment has been identified as a major factor that limits the potential of hand scanning. When that is the case, scanning is considered to be suitable for work activities that do not take place spontaneously and that are based on pre-compiled data that can be transferred to the scanner.
Keywords: Handskanner, Informationssystem, Användbarhet, Investeringskalkylering, Manuella monteringsflöden, Automation